2020
DOI: 10.3389/fonc.2020.530382
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates, Glycemic Index, and Glycemic Load in Relation to Bladder Cancer Risk

Abstract: Objective: Epidemiologic studies investigating the association between dietary carbohydrates as well as glycemic index and glycemic load (markers of carbohydrate quality) and bladder cancer risk have yielded inconsistent results. The aim of the present meta-analysis is to summarize the evidence on this association. Materials and Methods: A comprehensive literature search of articles published by December 2019 was performed in PubMed, Scopus, and Web of Science databases. A random-effects model was used to calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Dysbiosis is disturbances in the function and composition of the microbiota driven by environmental and host-related factors ( Leshem et al., 2019 ). This process may be involved in the pathogenesis of many diseases, such as IBD, IBS ( Cui et al., 2021 ), multiple sclerosis ( Engen et al., 2020 ; Li et al., 2020 ), hepatic encephalopathy ( Kao et al., 2016 ; Madsen et al., 2021 ), cancer ( Chen et al., 2019 ; Kaźmierczak-Siedlecka et al., 2020 ; Zhu H. et al, 2020 ) and metabolic syndrome ( Yu et al., 2020 ). Targeting the disturbed microbiota, which may be achieved by dietary interventions, probiotics, prebiotics, antibiotics, and FMT, might affect the progress of these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysbiosis is disturbances in the function and composition of the microbiota driven by environmental and host-related factors ( Leshem et al., 2019 ). This process may be involved in the pathogenesis of many diseases, such as IBD, IBS ( Cui et al., 2021 ), multiple sclerosis ( Engen et al., 2020 ; Li et al., 2020 ), hepatic encephalopathy ( Kao et al., 2016 ; Madsen et al., 2021 ), cancer ( Chen et al., 2019 ; Kaźmierczak-Siedlecka et al., 2020 ; Zhu H. et al, 2020 ) and metabolic syndrome ( Yu et al., 2020 ). Targeting the disturbed microbiota, which may be achieved by dietary interventions, probiotics, prebiotics, antibiotics, and FMT, might affect the progress of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We used the DerSimonian and Laird random-effects models to recalculate the pooled effect sizes using STATA V.14. ( Zhu J. et al, 2020 ). We did not review the primary study included in each meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysbiosis is disturbances in the function and composition of the microbiota driven by environmental and host-related factors 12 . This process may be involved in the pathogenesis of many diseases, such as IBD, IBS 44 , multiple sclerosis 45, 46 , hepatic encephalopathy 47, 48 , cancer 49-51 and metabolic syndrome 52 . Targeting the disturbed microbiota, which may be achieved by dietary interventions, probiotics, prebiotics, antibiotics, and FMT, might affect the progress of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous publications of different cancers showed discrepant results. For example, some studies reported that GI and GL might be associated with the risk of bladder, breast, gastric, colorectal, and ovarian cancers; however, no significant association for pancreatic cancers [15][16][17][18][19][20]. Two meta-analyses have examined the relationship between GI or GL and lung cancer risk [21,22]; however, these articles have limitations, such as insufficient included studies, unexplained heterogeneity sources, and excluded case-controlled studies.…”
Section: Introductionmentioning
confidence: 99%